O ciclo vigília/sono dos(as) alunos(as) na organização do trabalho docente: as particularidades do corpo nas cenas da aula - Novais, Eliane Santana (2011)
This search presents the results of the relationship between sleep/wake cycle, teacher job and favorable learning conditions. It was done a case study with 11 to 13 years old students in a sixth grade of morning shift Basic School class and their teachers. Search questions were: what is the meaning of students sleep/wake cycle (SWC) in teachers job organizing? Which proceedings, space organizing and time use can be chosen to fit teachers job and which are their meaning concerning to the needs determined by students SWC in order to constitute favorable conditions for school learning? A bibliographic study was performed as well a field one. Teacher job was based on the ideas of Marx (1974), Saviani (2003) and Frigotto (2009). Chronobiology formulations from Marques & Menna-Barreto (1997; 2003); Louzada & Menna-Barreto (2007); Andrade (1991; 1997) and Mello (1999) were also used. For data collection we used sleep habits questionnaire, children and class Horne & Ostber s sleeping diaries, semi-structured interviews, chats and observation. The results allowed us to perceive the explicative potential of job category and how pertinent is using it to elucidate the search questions. So that teachers job, which was previous considered as a not material one, was materialized through routines and ways of occupying class time and space articulated to other social practices. It collaborated to this search, by not including the students physical needs, especially concerning to SWC in its organization, in order to make learning easier. The students were mostly afternoon individuals but they studied in the morning and were often underwent to activities resulting from a homogenous, hierarchical and fragmented teaching job, strongly linked to the body disciplining. Failing of 45.3% of sleepy students allow us to discuss partial sleep deprivation as one of the elements in the set of the set of inadequate teaching and learning proceedings. The results suggest a relationship between inadequate school time, teacher job, students SWC and learning conditions. The search allowed us to indicate the importance of including SWC knowledge in teaching formation as well to discuss teacher job organization in order to respect the students special conditions, creating conditions to teach and identifying a quality teaching as a human right of each student.